CONTRIBUTION OF SPECIALISTS IN THE SADF - Ackron, J.C. (Scientia Militaria - South African Journal of Military Studies, 2012)
I would like to contribute to the debate on the article 'DIE AKADEMIKUS SE PLEK IN DIE SAW' (Militaria 8/4 of 1978) with the following observations: